Differences in the Effect of Circuit Training and Fartlex Training on Increasing Vo2Max of Pencak Silat Athletes - Kamarudin, Kamarudin; Sasmarianto, Sasmarianto; Rahmalia, Wahyuni (Indonesian Journal of Physical Education and Sport Science, 2024)
Study Purpose. The purpose of this study was to determine the difference in the effect between circuit training and fartlek training in increasing VO2Max for pencak silat athletes. Materials and Methods. This study uses experimental research methodology with independent variables of circuit training and fartlek training, the dependent variable is VO2Max. The sample in this study amounted to 26 martial arts athletes with total sampling. Circuit training exercises have an effect on increasing VO2Max, then Fartlek training has an effect on increasing VO2Max. Results. The results of the value of the two tests obtained a value of 0.00 <0.05 circuit training and farlek training of 0.01 <0.05. before and after being given exercise treatment it can be concluded that the results obtained by circuit training and Fartlex Exercise Influence on Increasing VO2Max athletes who are significant. Conclusion. Based on the results of research and data analysis, it can be concluded that circuit training has a significant effect on increasing VO2Max, fartlek training has a significant effect on increasing VO2Max. when viewed from these two exercises, fartlek training has a more significant effect on increasing VO2Max for Pencak Silat athletes.